Systemic lupus erythematosus and the risk of cardiovascular diseases: A two-sample Mendelian randomization study - Huang, Shuo; Huang, Fugang; Mei, Chunyun; Tian, Fengyuan; Fan, Yongsheng; Bao, Jie (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous observational studies suggested that the association between systemic lupus erythematosus (SLE) and cardiovascular diseases (CVDs) remained inconsistent. In this study, we aimed to investigate the causal relationship between SLE and CVDs by two-sample Mendelian randomization (MR) analysis. Methods: Genetic instruments for SLE were obtained from a public genome-wide association study (GWAS) with 4036 SLE patients and 6959 controls. Summary statistical data for CVDs, including coronary artery disease (CAD), myocardial infarction (MI), atrial fibrillation (AF), ischemic stroke (IS) and its subtypes, was identified from other available GWAS meta-analysis. The inverse-variance weighted (IVW) method, as the primary method, was applied to estimate the causal effect. Besides, we performed the sensitivity analyses, including the simple- and weighted-median method, MR-Egger regression, the MR pleiotropy residual sum and outlier (MR-PRESSO) method and Leave-one-out analysis, to evaluate the robustness of our MR results. Results: After excluding linkage disequilibrium (LD) and potential confounding factors, a total of 15 SNPs were identified. According to the IVW results, our MR study indicated that genetically predicted SLE was not causally connected with the risk of CVDs [CAD: odds ratio (OR) = 1.005, 95% confidence interval (CI) = 0.986-1.024, p-value = 0.619; MI: OR = 1.002, 95% CI = 0.982-1.023, p-value = 0.854; AF: OR = 0.998, 95% CI = 0.982-1.014, p-value = 0.795; IS: OR = 1.006, 95% CI = 0.984-1.028, p-value = 0.621; cardioembolic stroke (CES): OR = 0.992, 95% CI = 0.949-1.036, p-value = 0.707; small vessel stroke (SVS): OR = 1.014, 95% CI = 0.964-1.067, p-value = 0.589; large artery stroke (LAS): OR = 1.030, 95% CI = 0.968-1.096, p-value = 0.352]. Analogical findings could be observed in other MR methods as well. And sensitivity analyses also suggested the causal estimate was robust. Conclusion: Our two-sample MR analysis provided little evidence that genetically determined SLE was causally associated with the risk of CVDs.